Objective Liability and Consumer Protection in Land Public Transport - Sepriani, Sarnida (Jurnal Ilmu Hukum Kyadiren, 2025)
The loss of passenger luggage stored in cabin compartments during land transportation raises significant questions regarding the legal responsibility of public transportation companies. This study analyzes the legal liability of PT. Rosalia Indah Transport for passenger losses, examines the available compensation mechanisms under Law No. 22 of 2009 on Road Traffic and Transportation and Law No. 8 of 1999 on Consumer Protection, and offers normative recommendations for enhancing consumer protection in this sector. Utilizing a normative legal research approach, this study is based on statutory analysis and case studies. The findings demonstrate that transportation operators bear objective liability for passenger belongings under their supervision, and that compensation may be pursued through both non-litigation and litigation channels. The study concludes that the current system of legal responsibility and dispute resolution remains inadequate and requires procedural reforms to ensure fairness, transparency, legal certainty, and effective consumer protection in public transportation services.